Low pressure solubilities of CO2 in guanidinium trifluoromethanesulfonate-MDEA systems - Sairi, Nor Asrina; Abd Ghani, N.; Aroua, M.K.; Yusoff, R.; Alias, Y. (Elsevier, 2015)
It is an urgent act to limit greenhouse gas emissions to avoid the harmful effects of climate changes. In this work, the binary and ternary systems of guanidinium trifluoromethanesulfonate (guaOTf) in N-methyldiethanolamine (MDEA) and/or water were examined as alternative solvents for gas treatment process. The thermodynamic properties including density, rho, viscosity, eta, thermal expansion, alpha(p) and physical solubility of CO2 in the systems were measured as a function of molar composition with a temperature range of 293.2-333.2K at 100-1000 kPa. The presence of guaOTf accelerates CO2 absorption process. The present study offers equations of correlation providing a reliable prediction of the binary and ternary systems as a function of concentration. The linear equation, quadratic equation, extended Arhenius equation and Henry's Law equation have been applied to assess the validity of the finding. The CO2 solubilities in guaOTf systems are found higher compared to other ILs in previous researches. Additionally, ANN modeling of the effective parameters was carried out and the composition of guaOTf was proven as the key factor in maximizing the CO2 solubility. (C) 2014 Elsevier B.V. All rights reserved.